Volunteer Service and Well-Being of Older People in China - Yang, Hua-lei; Zhang, Shuo; Zhang, Wen-chao; Shen, Zheng; Wang, Jia-hao; Cheng, Si-meng; Tao, Yi-wen; Zhang, Si-qing; Yang, Li-xingzi; Yao, Yi-dan; Xie, Lin; Tang, Li-li; et al. (Frontiers in Public Health, 2022)
Purpose The social support theory suggested that involving older people in social activities could increase their level of social participation and interaction, which in turn improved their well-being. However, there has been a heated controversy about whether participating in volunteer services could enhance the well-being of older people, especially for the Chinese sample. Method Based on the data from the China Health and Retirement Longitudinal Study (CHARLS) in 2013, this paper used an ordered probit model to examine the impact of older people's participation in volunteer services on their well-being, as well as the differences in the impact across groups and the specific transmission mechanism. Result The empirical study found that Chinese older people's participation in volunteerism significantly enhanced their well-being, which remained robust after eliminating the possible effects of self-selection. Further heterogeneity analysis revealed that for female, non-party members and older adults with good economic status, participation in volunteerism has a higher increase in well-being. The mediating effect test indicated that older people's participation in volunteerism affected well-being mainly through enhancing positive emotions. Conclusion It is necessary to promote the participation of older people in volunteer services and to clarify the role of government support and advocacy. Proper guidance is given to change the role of older people as care recipients to that of service providers and caregivers, and to continuously enrich the programmes and content of volunteer service to safeguard the well-being of older people.